2019
DOI: 10.1155/2019/6067312
|View full text |Cite
|
Sign up to set email alerts
|

Ligament Reconstruction for Recurrent Anterior Dislocation of the Radial Head

Abstract: Isolated recurrent dislocation of the radial head (RH) is very rare, and there have been few reports describing the surgical treatment of this injury. We herein report the case of a 13-year-old girl who underwent ligament reconstruction surgery for isolated recurrent RH dislocation. Her symptoms included pain and apprehension at the elbow with the forearm in supination. A radiologic examination revealed anterior dislocation of the RH with the forearm in supination but complete reduction with the forearm in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…As with the previous cases, 4 , 7 the dislocation in our case was occurred when the forearm was supinated, and insufficiency of annular ligament might be involved in the dislocation according to the radiographic and intraoperative findings. Given the cause of the dislocation, the pathogenesis of our cases might be identical with Hatta’s case because both cases had no history of obvious trauma.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As with the previous cases, 4 , 7 the dislocation in our case was occurred when the forearm was supinated, and insufficiency of annular ligament might be involved in the dislocation according to the radiographic and intraoperative findings. Given the cause of the dislocation, the pathogenesis of our cases might be identical with Hatta’s case because both cases had no history of obvious trauma.…”
Section: Discussionsupporting
confidence: 76%
“…Hatta et al reported a 13-year-old female basketball player who recognized pain and apprehension with prominence at the anterolateral elbow. 4 Unlike the Salama and Itadera’s cases, there was no history of major trauma around the elbow. The patient recognized asymptomatic stiff prominence at the anterolateral aspect of elbow for 3 years before the symptom occurred.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 8 found that annular ligament repair was not essential in the operative treatment of isolated radial head fractures when the lateral collateral ligament was intact. Other scholars believe that annular ligament repair makes the elbow joint more stable and reduces the pain and injury caused by elbow joint instability in later periods 9 , 10 , 11 , 12 , 13 . Bhaskar 10 found that the need for annular ligament reconstruction was based on intraoperative findings of radial head instability for missed Monteggia fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars believe that the elbow joint can function well without annular ligament repair (6)(7)(8). Other scholars believe that annular ligament repair can make the elbow joint more stable and reduce the pain and injury caused by elbow joint instability in later periods (9)(10)(11)(12)(13).Therefore, further understanding of the role of the annular ligament in elbow joint stability is particularly important. At present, there are few studies on the biomechanics of the annular ligament (14) , and most of them focus on the influence of elbow joint dislocation, deformity and fracture on elbow joint stability, while the role of the annular ligament in maintaining elbow joint stability has been ignored.…”
mentioning
confidence: 99%